Análisis de la violencia psicológica y física contra la mujer en el ámbito intrafamiliar o doméstico y los efectos en su entorno - Loaiza Chamba, Daniela Michelle (2023)
The undergraduate research titled "Análisis de la Violencia Psicológica y Física contra la Mujer en el Ámbito Intrafamiliar o Doméstico y sus Impactos en el Entorno” “Analysis of Psychological and Physical Violence against Women in the Intrafamily or Domestic Sphere and its Impacts on the Environment" addresses the lack of public policies for protecting women who experience domestic violence. It is critical to highlight that psychological violence is equally detrimental as physical violence, as its effects can be severe and long-lasting. Detecting psychological violence promptly can prevent further damage to women and guarantee their rights are protected. The research shows that aggressors are not born as such, but in many cases, these violent behaviors emerge from traumatic experiences during their childhood, parental influence, or other factors. The offender becomes convinced that such conduct is normal and seeks to maintain this rooted mindset. It leads them to believe they have rights over their partners and act dominantly, expecting women to comply with their desires and remain silent. Social evolution has allowed women to claim their rights and refuse submissiveness. However, many victims of psychological violence still find themselves trapped in relationships where the aggressor aims to control them, depriving them of their freedom. Therefore, this research focuses on raising awareness among women suffering from physical and psychological violence, urging them to report and end any kind of abusive treatment. Women are not objects to be controlled by aggressors; it is essential for them to demand respect; so, laws and public policies should be designed to empower and provide the necessary support. To conduct this research paper, a diverse set of materials and methods were utilized, including interviews and surveys involving legal professionals and clinical psychologists. The obtained results facilitated the formulation of a legal proposal with the purpose of fortifying protection and raising awareness on this issue, while also seeking to reversing acts of superiority exercised by men over women.